Profit shifting by multinational corporations: Evidence from transaction-level data in Nigeria - Bathusi Gabanatlhong; Javier Garcia-Bernardo; Paulinus Iyika; Miroslav Palanský (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Research on profit shifting by multinational corporations in developing countries is limited due to a lack of data. In this paper we use, for the first time, novel administrative data on the transactions of multinational corporations operating in Nigeria vis-à-vis related parties in other jurisdictions. The data provides a breakdown of these intra-group transactions into seven categories: (1) tangible goods, (2) services and fees, (3) royalties, (4) interest, (5) dividends, (6) reimbursements, and (7) other. We develop a methodology that uses this data to identify which transactions are most often used by multinationals to shift profits out of Nigeria and estimate their relative importance. We find that profits reported in Nigeria are highly sensitive to the hypothetical tax that would be paid on a transaction's value in the partner jurisdiction: a 1 per cent increase in the hypothetical tax on outgoing transactions is associated with a 0.28 per cent increase in reported profits in Nigeria. Payments for services and fees, royalties, and interest going from Nigerian companies to affiliates in low-tax countries are the most important channels of profit shifting in Nigeria. We argue that our approach can be used to inform low-cost policy interventions and increase audit efficiency with potentially strong effects on corporate income tax collection.
Keywords: F36; G28; H26; H87; 330; tax havens; multinational corporations; profit shifting